Spontaneous Expulsion of Lower Ureteric Stones in Patients with Elevated Level of C-Reactive Protein - Haris Hamid, Israr Ali, Rafi Ullah, Akhtar Ghani, Zubaida Khanum Klazir, Sibghat Ullah, Muhammad Ijaz Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Around 4–15% of people worldwide have urolithiasis, and ureteric stones account for around 20% of this condition. One of the most frequent situations a urologist has to deal with is acute renal colic caused by urolithiasis. Objective: To determine the spontaneous expulsion of lower ureteric stones in patients with elevated level of c-reactive protein Methodology: This descriptive cross sectional study was performed at the urology department Khalifa Gul Nawaz Teaching Hospital, Bannu Medical College Bannu for a period of six months from January 2022 to June 2022. A total of 210 patients were included in the study using non probability consecutive sampling. All patients had lower ureteric stone and raised CRP. Patients were followed till spontaneous expulsion or stone clearance. Data was analyzed using IBM SPSS version 23. Results: A total of 210 patients were enrolled in this study. There were 112(53.33%) were female and 98(46.67%) were male. Patients included in the study had age range from 18- 60yr,mean age was 34.32±7.92 SD. Patients selected in the study had lower ureteric stones ranging from 5-9mm. mean stone size was 6.990 mm ±0.92 SD. Mean CRP was 3.36 mg/dl ±1.99 SD. 50 (31.25%) patients with CRP 0.5-4.9mg/dl passed stones spontaneously while 45 (90%) patients with CRP 5-9.9 mg/dl passed stone spontaneously. Conclusion: Serum CRP is a relatively newer marker now increasingly being used for the purpose of predicting spontaneous stone expulsion of small lower ureteric stones. However current evidence still does not support CRP levels alone to be recommended for this purpose. Clinical assessment of every individual patient is still the mainstay of decision for intervention. Keywords: Spontaneous expulsion; lower ureteric stones; c-reactive protein